Accounting information systems - Romney, Marshall B. (Pearson Education Limited, 2018)
For undergraduate and graduate courses in Accounting Information Systems (AIS). A market-leading text with the most comprehensive, flexible coverage of AIS available. 'Accounting information systems' delivers the most comprehensive and flexible coverage of each major approach to teaching AIS, giving instructors the opportunity to reorder chapters and focus the material to suit their individual course needs. The 14th Edition covers all of the most recent updates in AIS, including how developments in IT affect business processes and controls, the effect of recent regulatory developments on the design and operation of accounting systems, and how accountants can use the AIS to add value to an organization. Not only will students see how AIS has changed the role of an accountant, but they'll also be prepared for a successful accounting career in public practice, industry, or government.